Sarah Kane e o teatro in-yer-face: a poética do excesso contra o percepticídio nas peças Blasted (1995) e Cleansed (1998) - Pantaleão, Débora Gil (2022)
The playwright Sarah Kane is considered by Aleks Sierz as the author who inaugurated the In-Yer-Face Theatre with her first play, Blasted (1995). This theatre, which dramatises violence in excess and exposes the most perverse forms of cruelty to spectators, would be continued with the author’s second play – Cleansed (1998) – part of a trilogy never completed by Kane. During the production of the plays, and due to the aggressive responses of the British media to her theatre, the author had to start using a pseudonym when writing this second piece of the unfinished trilogy. In this scenario of a dramaturgy marked by excesses and deprivations, our objective was to analyse Sarah Kane’s poetics of excess as an aesthetic choice that imposes itself against percepticide, positioning itself as a rejection and resistance to what can and cannot be seen and perceived in our social structures. To verify the validity of this hypothesis, we analysed Kane’s socio-historical context with the Thatcher Era and the Tony Blair government and the facts that demonstrate that Cool Britannia was a Cruel Britannia; we work on Sierz’s definitions of In-Yer-Face Theatre as a locus of transgression of mainstream theatre; in addition to presenting Kane’s work, in the first chapter. In the second chapter, we examine characteristics of postmodernity and postmodernism through Jameson (1991), Anderson (1999) and Maffesoli (2003, 2016) to name a few. For the study of parody and irony in postmodernism, we examine the contributions of Linda Hutcheon (1985, 2000, 2001) and Afonso Romano de Sant’Anna (2004). The need to think about the tragic nature of Kane’s plays sent us to Raymond Williams (2002). To think about violence in postmodernity from the perspective of the victims, we use the concept of “horrorism” by the Italian philosopher Adriana Cavarero (2009). We articulate Cavarero’s thoughts with those of Judith Butler (2018, 2020), who deals with vulnerable and non-mourning beings, to name the bodies that suffer and that experience the postmodern tragic. We conclude that, in Kane’s plays, it is through the “anti-structure” that such beings can become visible, that is, through parody and irony in re-presenting the real as pastiche. The tensions around the ambiguity brought by Jameson are appeased in our analysis through the study of irony, since it deals with the reader or spectator capturing the ironic game and realising what is set to be seen and denounced – through the excess of violence – in theatrical plays. That said, it is clear that the dominant postmodern aesthetics emphasises the parodic and ironic almost as the only possible way out of absurdity and social discontent.